Penggunaan Instructional Coaching untuk Meningkatkan Kompetensi TPACK Guru Kelas II - Astuti Apriliantari; Hery Winoto Tj; Takim Andriono (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to enhance the TPACK (Technological Pedagogical Content Knowledge) competencies of second-grade teachers at Petra Christian Elementary School 10 in Surabaya through the use of Instructional Coaching. TPACK is a framework that integrates technological knowledge, pedagogical knowledge, and content knowledge to develop effective teaching practices. Instructional Coaching is a coaching approach that involves collaboration between teachers and coaches to improve teaching practices and student learning outcomes. The research method used is classroom action research (CAR) with a spiral design consisting of four stages: planning, action, observation, and reflection. The study involves six second-grade teachers as research subjects. The results of the study show that through the Instructional Coaching process, there was a significant increase in teachers' TPACK competencies. Teachers became more proficient in integrating technology into their teaching, understanding how technology can support effective pedagogy, and enhancing their content knowledge. The conclusion of this study is that Instructional Coaching is an effective strategy for enhancing the TPACK competencies of second-grade teachers at Petra Christian Elementary School 10 in Surabaya. Recommendations are given to schools to continue implementing and developing teacher TPACK competencies through this coaching program in order to improve the quality of education.